The development of a numeracy e-module on geometry for junior high school students - Khairina Khairina; Widdatul Hasanah; Nuralam Syamsuddin (AXIOM : Jurnal Pendidikan dan Matematika, 2025)
Numeracy skills are essential for daily life and must be mastered by students. However, data from PISA and TIMSS indicate that Indonesian students' numeracy skills are still low. One contributing factor is the limited availability of numeracy-based learning materials, which reduces students' familiarity with numeracy-oriented problems. Therefore, this study aimed to develop a numeracy e-module on geometry for eighth-grade junior high school students. This study employed a research and development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The participants included students and teachers from SMPN 2 Banda Aceh. Data were analyzed using qualitative techniques to describe interview results and quantitative techniques to analyze validation, readability, and practicality data. The results showed that the e-module achieved an average score of 4.37 for material presentation and assessment and 4.53 for media and language aspects, both categorized as very valid. The practicality evaluation indicated positive responses, with average scores of 4.46 from teachers and 4.35 from students, both categorized as very practical. These findings indicate that the developed numeracy e-module on geometry is valid and practical for use in junior high school mathematics learning.